Rising Powers, Status Ambitions, and the Need to Reassure: What China Could Learn from Imperial Germany's Failures. (8th May 2014) - Wolf, Reinhard
Abstract: This article focuses on the ominous parallels between the rise of Germany before World War I and China's ongoing ascendance. It will demonstrate that concerns about national status strongly affected both the fateful escalation of the 1914 crisis and the growing antagonisms of the years preceding. Special emphasis will be given to the role that mutual 'misrecognition' played in the gradual deterioration of Anglo–German relations. The consequences of Germany's excessive fixation on status are highly relevant for contemporary China, due to the startling similarities between both countries' domestic and international settings. If China wants to avoid the policy errors that led to the Kaiserreich's self-encirclement it needs to pay more attention to dangerous feedbacks among ongoing power shifts, maritime security dilemmas and extravagant public status concerns. China should do more to ensure that external trust in its benign intentions grows faster than its international ambitions and military power. This requires, among other things, an early settlement of ongoing territorial disputes, a toning down of jingoistic domestic discourses, enhanced leeway for speakers advocating international cooperation, and higher investment in multilateral institutions. Beijing's partners, for their part, must encourage such self-binding policies by facilitating China's rise in status, specifically by giving Beijing a greater say in these institutions.